Life-history traits of Drosophila melanogaster populations exhibiting early and late eclosion chronotypes - Nikhil, K. L. (BMC Evol Biol, 2016)
BACKGROUND: The hypothesis that circadian clocks confer adaptive advantage to organisms has been proposed based on its ubiquity across almost all levels of complexity and organization of life-forms. This thought has received considerable attention, and studies employing diverse strategies have attempted to investigate it. However, only a handful of them have examined how selection for circadian clock controlled rhythmic behaviors influences life-history traits which are known to influence Darwinian fitness. The ‘early’ and ‘late’ chronotypes are amongst the most widely studied circadian phenotypes; however, life-history traits associated with these chronotypes, and their consequences on Darwinian fitness remain largely unexplored, primarily due to the lack of a suitable model system. Here we studied several life-history traits of Drosophila melanogaster populations that were subjected to laboratory selection for morning (early) and evening (late) emergence. RESULTS: We report that the late eclosion chronotypes evolved longer pre-adult duration as compared to the early eclosion chronotypes both under light/dark (LD) and constant dark (DD) conditions, and these differences appear to be mediated by both clock dependent and independent mechanisms. Furthermore, longer pre-adult duration in the late chronotypes does not lead to higher body-mass at pupariation or eclosion, but the late females were significantly more fecund and lived significantly shorter as compared to the early females. CONCLUSIONS: Coevolution of multiple life-history traits in response to selection on timing of eclosion highlights correlations of the genetic architecture governing timing of eclosion with that of fitness components which suggests that timing ecologically relevant behaviors at specific time of the day might confer adaptive advantage. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12862-016-0622-3) contains supplementary material, which is available to authorized users.